CompTIA Security+ (SY0-501) : complete video course - Greene, Sari Stern, 1957- (LiveLessons (Indianapolis, Ind.), 2017)
CompTIA Security+ (SY0-501) Complete Video Course is an engaging self-paced video training solution that provides learners with more than 19 hours of personal training from security expert Sari Greene. Through the use of topic-focused instructional videos, you will gain an in-depth understanding of each objective in the CompTIA Security+ (SY0-501) exam as well as a deeper understanding of security foundations and principles. CompTIA Security+ (SY0-501) Complete Video Course contains more than 19 hours of training with content divided into 7 modules with more than 40 content-targeted lessons. This title covers every objective in the newly updated CompTIA Security+ SY0-501 exam and includes screencast teaching, whiteboard explanations, deep dives on security theory and everyday practices, and live demos/labs showing how to complete tasks in real time. Most lessons end with a "Security in Action" segment, which takes the security knowledge you’ve learned to the next level. The video lessons in this course review each exam objective, so you can use it as a complete study tool for taking the CompTIA Security+ exam.